Comparative Analysis of Murabahah and Mudharabah Financing Risk from Islamic Microfinance Institutions Perspective - Azhar Alam; Raditya Sukmana; Bayu Arie Fianto; Azzam Izzuddin (AL-MUZARA'AH, 2022)
The most frequently used financing contracts in Islamic financial institutions are murabahah and mudharabah. This study aims to reveal the phenomenon in the field about the description of the risk comparison between murabahah financing and mudharabah financing from the BMT side. This study uses descriptive qualitative research methods through data collection methods with in-depth interviews with nine respondents who have experience handling the risks of murabahah financing and mudharabah financing at BMT. This study shows that the risk of mudharabah financing is greater than the risk of murabahah financing. In practice, mudharabah financing tends to be relatively high due to asymmetric information and moral hazard. The inherent risk in murabahah financing is the risk of member default due to default or member negligence in returning installments. This study also identifies risk factors such as trust risk and sharia legal risk for murabahah financing with wakalah contracts. This study shows that BMT applies the precautionary principle and is appropriate to maintain the institution's health to minimize the risks that occur. This research is expected to be a reference in managing the risk of murabahah financing and mudharabah financing with innovative strategies. The BMT Islamic Microfinance Institution needs to stimulate and educate to reduce the risk of mudharabah financing so that it can become a top priority for financing.